It Is Time to Factor Natural Disasters into Macroeconomic Scenarios - Thomas, Vinod (World Bank, Washington, DC, 2012)
Over the recent year, humanity has faced natural disasters of unprecedented magnitude and impact. However, governments and international aid organizations do not systematically plan for preventing and mitigating the effects of natural disasters, and macroeconomic scenarios seldom take into account the results of their increasing incidence, damages, and costs. Using evaluative lessons from the World Bank's and others' experience, this note highlights the urgent need to invest in climate change mitigation, disaster preparedness, early response, and post-disaster reconstruction.